ANALISIS PENERAPAN AKUNTANSI KOPERASI SIMPAN PINJAM MENURUT SAK ETAP PADA KOPERASI SURU PUDI KOTING - Priska Toyo, Febriana; Niken Aurelia, Pipiet; Patty, Thadeus Fransesco Quelmo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research is against the background of the problem of Analysis of the Application of Accounting for Savings and Loans Cooperatives According to SAK ETAP at the Suru Pudi Koting Cooperative. This study aims to determine the application of accounting based on Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) at the Suru Pudi Koting Cooperative. This study used a qualitative descriptive method. Data was obtained through interviews and documentation. Key informants are managers and finance staff of the Suru Pudi Koting Cooperative. Data is obtained using data collection, data reduction, data presentation, and conclusion drawing or data verification. The results of this study show that the Suru Pudi Koting Cooperative does not fully implement entity financial accounting standards without public accountability (SAK ETAP). This can be concluded by: 1) the financial statements that have been presented by the Suru Pudi Koting Cooperative only consist of a balance sheet and a report on the calculation of operating results. 2) Suru Pudi Koting Cooperative does not prepare statements on changes in equity, cash flow statements, and notes to financial statements.